Steady flow in a linearly diverging asymmetrical channel - Makinde, Oluwole Daniel (Computer Assisted Methods in Engineering and Science, 2023)
In this paper the steady flow of a viscous incompressible fluid in a slightly asymmetrical channel is considered. The flow is considered for channel with a small aspect ratio . The solution is expanded into a Taylor series with respect to the Reynolds number. Using the D-T method (Drazin and Tourigny, [7]), a bifurcation study is performed. Parameter ranges for the Reynolds number, where no, one or two solutions of the given type exist, are computed.